Characteristics of ethidium uptake by the trypanosomatid flagellates Crithidia fasciculata and Leptomonas seymouri. - Coolbear, K P (1986)
The uptake of the phenanthridinium ethidium by the trypanosomatids Crithidia fasciculata and Leptomonas seymouri was studied. The time course of uptake of ethidium was biphasic for both organisms, consisting of an initial rapid phase and a protracted slow phase. The characteristics of these phases were consistent with the hypothesis that the initial phase represented specific external binding, while the second phase represented transport into the cells. In L. seymouri the transport phase was inhibited by inhibitors of energy transduction and putative inhibitors of a transport ATPase. Ethidium transport could not be saturated over a large concentration range of ethidium. Phenanthridiniums and related compounds displayed both inhibitory and stimulatory effects on ethidium transport.